Serum Metabolomics Analysis of the Anti-Inflammatory Effects of Gallic Acid on Rats With Acute Inflammation - Wu, Yue; Li, Kuangyu; Zeng, Maolin; Qiao, Boyang; Zhou, Benhong (Frontiers in Pharmacology, 2022)
Gallic acid(GA) is a natural small-molecule polyphenol that has a wide range of pharmacological activities. Until now, some works have studied the effect and the mechanisms of GA against inflammation. However, whether or how gallic acid regulates the downstream metabolic disorder in acute inflammation remains unclear. In the present work, a carrageenin-induced inflammation rat model and the metabolomics approach were employed to evaluate the therapeutic effects of GA on acute inflammation. Local swelling on paw and serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) were assessed. Serum metabolomics based on high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) was established to collect rats' metabolic profiles and explore the metabolic changes related to GA pretreatment. Compared to the Modal group, local pain, redness, and swelling in the rats' paws were significantly alleviated in GA groups. Dose-dependent decreases of TNF-α and IL-6 were also observed. Metabolomics analysis found significant alterations in metabolic signatures between the carrageenin-induced inflammation group and the control group. Twelve potential biomarkers were further identified in inflammation by principal component analysis (PCA) and partial least squares discrimination analysis (PLS-DA). In addition, when rats were pretreated with gallic acid, serum levels of eleven biomarkers were partially reversed. Metabolic pathway and networks analysis revealed that GA might invert the pathological process of acute inflammation by regulating the key biomarkers involved in linoleic acid metabolism, ascorbate and aldarate metabolism, pentose and glucuronate interconversions, and arachidonic acid (AA) metabolism pathways. These findings revealed the anti-inflammatory effect of GA against acute inflammation and the possible mechanisms in metabolism regulation